PENGARUH KEPEMIMPINAN, MOTIVASI KERJA, DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN (Studi Kasus Pada PT Luxindo Nusantara Kota Semarang) - Lestari, Oktafiana Nanda Budi; Nugraheni, Rini (Diponegoro Journal of Management, 2015)
Human resources is the main asset in every passage of the activity in the company. So that optimal attention should be given tothe employee. The background of this research is a decrease in the performance of employees at PT Luxindo Nusantara Semarang. Many factors that affect the performance of employees, including the leader who never involve subordinates in decision making, lack of reward and punishment system in the company that could affect employee motivation, and complaints from employees about the working environment that is not conducive so employees feel tired easily when working. Objective of this study was to prove the influence of leadership, motivation, and phsysical work environment on employee performance PT.Luxindo Nusantara SemarangÂ This study uses independent variables including leadership, motivation, and physical work environtment, as well as the dependent variable is the performance of employees. The population in this study were employees of PT.Luxindo Nusantara Semarang and samples taken were 72 respondents.Based on multiple linear regression analysis, the results showed that leadership, motivation, and physical work environment gives a significant positive effect on employee performance.